Erosion of Cu–W contact material of SF6 circuit breakers when making capacitor bank. Issue 2 (16th December 2019) - Ding, Can; Li, Chengxi; Fang, Chunhua
Abstract : For an SF6 circuit breaker in capacitor bank‐making operation, the inrush current may cause serious erosion to its arcing contacts. In order to observe the characteristics of this erosion, an arc extinguish chamber of SF6 circuit breaker with Cu–W arcing contacts was designed, and experiments of capacitor bank making were carried out. The prebreakdown arcing duration and inrush current were measured, and the mass loss of the contact after 100 times of operation was calculated. Power–frequency‐withstanding voltage was measured after every 20 operations. The surface status, scanning electron microscope (SEM), and energy dispersive x‐ray spectroscopy (EDS) of the contact material were recorded. The characteristics and mechanism of arcing contact erosion in SF6 circuit breaker in the making process were then analyzed. Compared to the case of breaking high current, this analysis found two major mechanisms that lead to severe arcing contact erosion in the case of capacitor bank making operation, namely, the arc erosion due to prebreakdown current and the erosion of arc heated contact due to friction. The erosion after contact caused by mechanical friction occupies a relatively larger proportion in the mass loss of contact materials. Under the conditions of 3 m/s making velocity, 18 kA current peak, and less than 2 ms arcing duration, the mechanical wear mass loss rate is greater than 1.0 mg/C. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.